(untitled) (Comprehensive Journal of Science, 2026)
The main source of pollution from internal combustion engines is nitrogen oxides and carbon oxides produced by the combustion process of fuel in the engine’s combustion chamber, and the exposure to these nitrogen oxides, which is exclusively present in the emissions from engines, comprises a mixture of nitric oxide (NO) and nitrogen dioxide (NO2), both of which pose substantial health risks. Nitric oxide is synthesized within the combustion chamber, specifically in regions characterized by elevated temperatures. Any methodology aimed at diminishing both the peak temperature and the concentration of oxygen present will subsequently lead to a reduction in the production of exhaust emissions. The quantity of crude oil reserves held by a nation has consistently been regarded as a vital indicator of that nation’s strength. The logical rationale for this perception is that oil constitutes the predominant industry that exerts a substantial impact on the global political landscape. This phenomenon results in an incessant demand for hydrocarbons, thereby necessitating perpetual petroleum production on a global scale. Petroleum, extracted from profound depths beneath the Earth’s crust, is subsequently refined into an array of valuable products, including gasoline, kerosene, diesel, asphalt, and liquefied petroleum gas (LPG). The World Petroleum Council (WPC) has projected that global consumption exceeds 100 million barrels daily, predominantly driven by engine-related sectors such as automotive, aviation, agriculture, mining, power generation, marine applications, and numerous others. Our modern society focuses on improving human mobility to allow access to many unexplored areas of the world. This has led to a rapid increase in vehicles powered by internal combustion engines that use fuels like propane, diesel, gasoline, or natural gas. The gasoline engine is the most common engine type worldwide, but it is also a major source of air pollution and smog. While it is important for transportation, the gasoline engine produces exhaust emissions as a result of burning fuel. These emissions include nitrogen (N2), water vapor (H2O), carbon dioxide (CO2), carbon monoxide (CO), unburned hydrocarbons (UHC), and nitrogen oxides (NOx). These chemicals can cause serious health problems over time and can sometimes even lead to death. For instance, carbon monoxide (CO) is a dangerous gas that is colorless, odorless, and tasteless but highly toxic. On the other hand, carbon dioxide (CO2) is one of several greenhouse gases that significantly affects global climate change. When nitrogen oxides (NOx) react with ammonia, they produce particulate matter and nitric acid vapor, which worsens respiratory issues like bronchitis.